2014
DOI: 10.1189/jlb.3mr0214-109r
|View full text |Cite
|
Sign up to set email alerts
|

Complement modulation of T cell immune responses during homeostasis and disease

Abstract: The complement system is an ancient and critical effector mechanism of the innate immune system as it senses, kills, and clears infectious and/or dangerous particles and alerts the immune system to the presence of the infection and/or danger. Interestingly, an increasing number of reports have demonstrated a clear role for complement in the adaptive immune system as well. Of note, a number of recent studies have identified previously unknown roles for complement proteins, receptors, and regulators in T cell fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 86 publications
1
45
1
Order By: Relevance
“…Thus, C1q–polarized phagocytic cells regulate T effector cell activation, essentially “sculpting” the adaptive immune response to avoid autoimmunity while clearing dying cells. While there have been some studies suggesting the possibility of a direct C1q interaction with T cells, more definitive investigations are needed (reviewed in (Clarke and Tenner, 2014)). The recent confirmation of the predominant role of C1q (rather than C1 activation and C3b deposition) on clearance and immunosuppression of apoptotic cells should direct therapeutic intervention in SLE and other autoimmune diseases (Colonna et al, 2016).…”
Section: Classical Functions: Complement Phagocytosis and Cytokinmentioning
confidence: 99%
“…Thus, C1q–polarized phagocytic cells regulate T effector cell activation, essentially “sculpting” the adaptive immune response to avoid autoimmunity while clearing dying cells. While there have been some studies suggesting the possibility of a direct C1q interaction with T cells, more definitive investigations are needed (reviewed in (Clarke and Tenner, 2014)). The recent confirmation of the predominant role of C1q (rather than C1 activation and C3b deposition) on clearance and immunosuppression of apoptotic cells should direct therapeutic intervention in SLE and other autoimmune diseases (Colonna et al, 2016).…”
Section: Classical Functions: Complement Phagocytosis and Cytokinmentioning
confidence: 99%
“…Recent studies have demonstrated its involvement in several physiological processes via binding with its specific receptors. 9 Among the processes induced by the non-classical functions of the C1q molecule, we find: the modulation of various immune cells, 10 the regulation of cell migration (chemotaxis), adhesion, survival and differentiation, 11 coagulation, 12 angiogenesis 13 and embryonic development, including neurological synapse function. 14 There is mounting evidence to support the idea that C1q and its receptors are also involved in the regulation of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It mediates the immune response against pathogens, by directly tagging them for clearance, and by triggering the expression of pro-inflammatory molecules and the activation and recruitment of immune cells at the site of infection. Furthermore, it is involved in the maintenance of tissue homeostasis and adaptive immunity (Clarke and Tenner, 2014; Nonaka and Kimura, 2006; Ricklin et al, 2010). Complement components are predominantly synthesized in the liver and circulate in the blood stream until their activation (Ricklin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%